The isotopic signature and distribution of particulate iron in the North Atlantic Ocean. (June 2015) - Revels, Brandi N.; Ohnemus, Daniel C.; Lam, Phoebe J.; Conway, Tim M.; John, Seth G.
Abstract: Iron (Fe) is a key micronutrient for life in the oceans. Particles play an important role in the marine biogeochemical cycling of Fe as a reservoir of marine Fe that may be directly accessible to phytoplankton, and as sources and sinks for seawater dissolved Fe. Here, we report the stable isotopic composition of Fe (δ 56 Fe) in suspended (0.8–51 μm) particles from the US GEOTRACES GA03 North Atlantic zonal transect, in order to facilitate a better understanding of the marine biogeochemical cycling of Fe. Data are presented both for a total digestion of the particles, and for 'ligand-leachable' phases of Fe using a newly-developed pH 8 oxalate–EDTA leach. For total particle digests, the mean δ 56 Fe across the whole GA03 section was 0.08±0.09‰ (1 S.D.) which is equivalent to the isotope composition of known lithogenic Fe sources to the ocean. In contrast, ligand-leachable Fe was generally lighter than continental material with a mean δ 56 Fe of −0.30±0.17‰ (1 S.D.). Our data also provide valuable insight into Fe biogeochemical cycling in several key regions. In the deep ocean, but above the depths where near-sediment nephloid layers are present, ligand-leachable Fe is isotopically lighter in the deep Western Basin compared to the deep Central and Eastern Basins suggesting differences in particle surface chemistry between resuspended seafloor sediments, which may predominate in the west, and Saharan dust that predominates in the center and in the east. Within a nephloid layer above reduced continental margin sediments in the Eastern Basin, below the Mauritanian upwelling region, we report the lowest particulate δ 56 Fe values for both total and ligand-leachable Fe, suggesting a transfer of isotopically light dissolved porewater Fe 2+ to the particulate phase. In contrast, δ 56 Fe values within a nephloid layer near Bermuda are similar to values higher in the water column. Within a hydrothermal plume sampled at the TAG hydrothermal field on the mid-Atlantic Ridge, decreasing Fe concentration and δ 56 Fe with distance from the vent indicate the water-column precipitation of Fe oxyhydroxides within the plume. Comparison between total and ligand-leachable particulate Fe concentrations throughout the transect also provides useful biogeochemical information. In the chlorophyll maximum, a high proportion of Fe in the labile phase demonstrates a relative lack of lithogenic material, while the high proportion of labile Fe observed between 2000 and 4000 m depth to the west of the mid-Atlantic Ridge suggests that hydrothermal oxyhydroxide particles can be transported thousands of kilometers away from vent sites. Throughout the North Atlantic, measurements of total and ligand-leachable Fe concentration and δ 56 Fe are therefore useful tools for studying the biogeochemical cycling of particulate Fe.